Plastic collapse load prediction of cracked circular hollow section T/Y-joints under in-plane and out-of-plane bending - Li, Tao (2019)
The plastic collapse loads of cracked circular hollow section (CHS) T/Y-joints under in-plane and out-of-plane bending are investigated using finite element (FE) analyses. An in-house 3D FE mesh generator is specifically developed to create the mesh models of the cracked joints containing a semi-elliptical surface crack located at the weld toe of the chord. Mesh convergence tests are then carried out to check the accuracy of the generated mesh models. The in-plane and out-of-plane plastic collapse moments of uncracked CHS T/Y-joints are calculated and compared with results obtained from three codes and experimental data. The comparison shows that the plastic collapse moments of uncracked CHS T/Y-joints obtained in this study are accurate and reliable. Subsequently, an extensive parametric study is carried out to investigate the plastic collapse moments of cracked CHS T/Y-joints under in-plane and out-of-plane bending. It is found that the in-plane and out-of-plane plastic collapse moments may decrease by up to 35.1% and 33.6% respectively when the crack area Anc reaches 25% of the intersectional area, t0*lw. Finally, two lower bound strength reduction factor FAR equations for cracked CHS T/Y-joints under in-plane and out-of-plane bending are proposed.